2017
DOI: 10.5812/jjnpp.55626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mosquito Repellent Activity of Nano-sized Microemulsion of Eucalyptus globulus Essential Oil Against Culicinae

Abstract: Background: The mosquitoes of Culicidae family are serious vectors of several tropical diseases, such as malaria, filariasis, encephalitis, and nuisance. Control of mosquitoes and protection of people from their bites are of the most important ways to prevent transmitted diseases. Although the efficacy of N, N-diethyl-m-toluamide (DEET) is high and generally used as mosquito repellent, yet a number of biting diptera are tolerant to DEET. Furthermore, there are concerns about the safety of DEET and its allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The protection time increased to 240 min when the concentration was 100 % . When Eucalyptus oil microemulsions were applied at concentrations of 5 %, 10 %, and 15 % w/w, the protection times for mosquitoes were 82±15.8, 135.7±26.4, and 170.7±26 min, respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protection time increased to 240 min when the concentration was 100 % . When Eucalyptus oil microemulsions were applied at concentrations of 5 %, 10 %, and 15 % w/w, the protection times for mosquitoes were 82±15.8, 135.7±26.4, and 170.7±26 min, respectively …”
Section: Resultsmentioning
confidence: 99%
“…[31] When Eucalyptus oil microemulsions were applied at concentrations of 5 %, 10 %, and 15 % w/w, the protection times for mosquitoes were 82 � 15.8, 135.7 � 26.4, and 170.7 � 26 min, respectively. [32] Insecticidal Activity of Essential Oil…”
Section: Repellent Activitymentioning
confidence: 99%
“…In a study consistent with the present study, Nuchuchua et al [5] reported that preparation of Nanoemulsion from citronella, hairy basil and vetiver essential oils increased their protection time of these essential oils to 4.7 hours. In a similar study by Sakulku et al, the results showed that the preparation of Nanoemulsions from citronella essential oil and the addition of glycerol greatly improved the physical appearance and stability of the emulsion and increased its protection time [30]. In another similar study, Mohammadi et al [21] reported that the preparation of Nanoemulsion from M. piperita and E. globulus significantly increased their protection and failure time.…”
Section: Repllentsmentioning
confidence: 92%
“…Lastly, Navayan et al showed how MEs could be a suitable tool to prolong the repellent activity of EOs [156]. In fact, 5%, 10% and 15% eucalyptus EO-based MEs showed a protection time against Culicidae of 82, 135 and 170 min, respectively, while free EO at the same concentrations showed lower time of activity, i.e., 34, 47 and 59 min, respectively.…”
Section: Green Micro- and Nanoemulsions As Insect And Tick Repellementioning
confidence: 99%